Immunotherapy toxicity in cancer: an oncology view for the internist - Ahmad Kanan, Ahmad Talat; López Ordoñez , Carolina; Riveros-Bermúdez , Sonia Dayana; Corredor-Rengifo , David (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Immunotherapy is considered one of the most recent advances in cancer treatment. Thanks to the technological advances developed in the last three decades in immunology and oncology, we have seen a promising uprising on the treatment of different oncological pathologies through the use of the patient's immune system, especially with the development of antibodies directed against various checkpoints of the immune system (Immune Checkpoint Blockade). A brief review of the pathophysiological mechanism of the most frequent irEAs reported in the literature will be done, as well as their incidence and prevalence according to the different immunotherapy drugs available for treating different solid and hematologic neoplasms.